Catalytic Response and Stability of Nickel/Alumina for the Hydrogenation of 5‐Hydroxymethylfurfural in Water. Issue 5 (12th February 2016) - Perret, Noémie; Grigoropoulos, Alexios; Zanella, Marco; Manning, Troy D.; Claridge, John B.; Rosseinsky, Matthew J.
Abstract: The catalytic response of Ni on Al2 O3 obtained from Ni–Al layered double hydroxides was studied for the liquid‐phase hydrogenation of hydroxymethyl furfural to tetrahydrofuran‐2, 5‐diyldimethanol (THFDM) in water. The successive calcination and reduction of the precursors caused the removal of interlayer hydroxyl and carbonate groups and the reduction of Ni 2+ to Ni 0 . Four reduced mixed oxide catalysts were obtained, consisting of different amount of Ni metal contents (47–68 wt %) on an Al‐rich amorphous component. The catalytic activity was linked to Ni content whereas selectivity was mainly affected by reaction temperature. THFDM was formed in a stepwise manner at low temperature (353 K) whereas 3‐hydroxymethyl cyclopentanone was generated at higher temperature. Coke formation caused deactivation; however, the catalytic activity can be regenerated using heat treatment. The results establish Ni on Al2 O3 as a promising catalyst for the production of THFDM in water. Abstract : Water as a solvent? The hydrogenation of 5‐hydroxymethylfurfural over Ni/alumina catalyst can result in exclusive formation of tetrahydrofuran‐2, 5‐diyldimethanol. The effect of water, reaction conditions, and catalysts composition on the catalytic response and stability are investigated.